Effect of Stoving and Air Drying Lacquers on Corrosion Resistance and Preserving Decorative Colours on Copper - Karaminezhaad, M.; Dadgarnezhad, A.; Baghaei, F. (Asian Journal of Chemistry, 2016)
The formation of patinas on copper surface is a subject of great interest, because of its aesthetic aspect and its protecting properties against the more diverse ambient conditions. In this study, the most important purpose is to produce various artificial patinas on copper surface and preserving them by applying clear lacquers. Different decorative colours have been produced by optimization of available conversion coating bath composition. Then, their corrosion resistances were evaluated in 3.5% NaCl solution before and after applying protective lacquers (stoving and air-drying) by using various techniques including electrochemical impedance spectroscopy, potentiodynamic polarization methods and salt spray test. The thicknesses of all coatings were almost the same (3-4 μm). The microstructure of coating surface was studied by scanning electron microscope (SEM) and surface composition was identified by X-ray diffraction (XRD). It was shown that the coating surface morphology (rather than its corrosion resistance) is an important factor for having a good protection after applying lacquers. The importance of this finding is the possibility of producing a range of colours by changing the porosity of the surface without reducing its corrosion resistance and even increasing it in some cases. The possibility of fine tuning the colour to the taste of the customer or the artist is its other aspect.